Combined effects of glycan chain length and linkage type on the immunogenicity of glycoconjugate vaccines - Chakkumkal Anish; Michel Beurret; Jan Poolman (npj Vaccines, 2021)
Abstract The development and use of antibacterial glycoconjugate vaccines have significantly reduced the occurrence of potentially fatal childhood and adult diseases such as bacteremia, bacterial meningitis, and pneumonia. In these vaccines, the covalent linkage of bacterial glycans to carrier proteins augments the immunogenicity of saccharide antigens by triggering T cell-dependent B cell responses, leading to high-affinity antibodies and durable protection. Licensed glycoconjugate vaccines either contain long-chain bacterial polysaccharides, medium-sized oligosaccharides, or short synthetic glycans. Here, we discuss factors that affect the glycan chain length in vaccines and review the available literature discussing the impact of glycan chain length on vaccine efficacy. Furthermore, we evaluate the available clinical data on licensed glycoconjugate vaccine preparations with varying chain lengths against two bacterial pathogens, Haemophilus influenzae type b and Neisseria meningitidis group C, regarding a possible correlation of glycan chain length with their efficacy. We find that long-chain glycans cross-linked to carrier proteins and medium-sized oligosaccharides end-linked to carriers both achieve high immunogenicity and efficacy. However, end-linked glycoconjugates that contain long untethered stretches of native glycan chains may induce hyporesponsiveness by T cell-independent activation of B cells, while cross-linked medium-sized oligosaccharides may suffer from suboptimal saccharide epitope accessibility.